Carta de ''Acting Judge Advocate'' en San Juan al ''Adjutant General'' - Todd, Roberto H.; Acting Judge Advocate (My University, 1899)
Carta que habla sobre el cambio de moneda.
Keywords: Money--Puerto Rico.; Moneda--Puerto Rico.